Gerakan Literasi dalam Pembelajaran Bahasa Indonesia Berbasis Kearifan Lokal Menuju Siswa Berkarakter - Aceng Joyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of writing is to describe the movement of literacy in Indonesian language learning based on local wisdom towards students characterized by using text close to the student environment. Problem-based research method and literature literature review. The result of the research shows that literacy movement in Indonesian language learning can be related to local wisdom considering that the values ​​prevailing in society are not fully understood by the students. The development of students character values ​​in Indonesian language subjects is done through learning language skills, namely writing and reading skills. In accordance with the purpose of learning Indonesian, which is to develop students competence in the use of Indonesian language in accordance with the context of student life. The utilization of learning resources based on local wisdom will affect the results and values ​​of the characters. Utilization of the texts of the observation of the existing environment near the students will affect the literacy movement of writing and reading. Keywords: Literacy, Local Wisdom, Character